Developing an online questionnaire authoring system - Zaw Tun (2008)
The study identifies the requirements for an online questionnaire authoring system which allows researchers to setup online questionnaires on the Web, records online responses and performs simple univariate and bivariate analyses. A prototype system was implemented using Microsoft SQL Server and Active Server Pages.